Monosomy 18p is a risk factor for facioscapulohumeral dystrophy. Issue 7 (21st March 2018) - Balog, Judit; Goossens, Remko; Lemmers, Richard J L F; Straasheijm, Kirsten R; van der Vliet, Patrick J; Heuvel, Anita van den; Cambieri, Chiara; Capet, Nicolas; Feasson, Léonard; Manel, Veronique; Contet, Julian; Kriek, Marjolein; et al.
Abstract : Background: 18p deletion syndrome is a rare disorder caused by partial or full monosomy of the short arm of chromosome 18. Clinical symptoms caused by 18p hemizygosity include cognitive impairment, mild facial dysmorphism, strabismus and ptosis. Among other genes, structural maintenance of chromosomes flexible hinge domain containing 1 ( SMCHD1 ) is hemizygous in most patients with 18p deletions. Digenic inheritance of a SMCHD1 mutation and a moderately sized D4Z4 repeat on a facioscapulohumeral muscular dystrophy (FSHD) permissive genetic background of chromosome 4 can cause FSHD type 2 (FSHD2). Objectives: Since 12% of Caucasian individuals harbour moderately sized D4Z4 repeats on an FSHD permissive background, we tested if people with 18p deletions are at risk of developing FSHD. Methods: To test our hypothesis we studied different cellular systems originating from individuals with 18p deletions not presenting FSHD2 phenotype for transcriptional and epigenetic characteristics of FSHD at D4Z4. Furthermore, individuals with an idiopathic muscle phenotype and an 18p deletion were subjected to neurological examination. Results: Primary fibroblasts hemizygous for SMCHD1 have a D4Z4 chromatin structure comparable with FSHD2 concomitant with DUX4 expression after transdifferentiation into myocytes. Neurological examination of 18p deletion individuals from two independent families with a moderately sized D4Z4 repeat identified muscle features compatible with FSHD. Conclusions: 18p deletions leading to haploinsufficiency of SMCHD1, together with a moderately sized FSHD permissive D4Z4 allele, can associate with symptoms and molecular features of FSHD. We propose that patients with 18p deletion should be characterised for their D4Z4 repeat size and haplotype and monitored for clinical features of FSHD.